4SCAR2.0 therapy for the management of post-transplantation relapse of B-cell acute lymphoblastic leukemia - Zhang, Rui; Xiao, Juan; Sun, Yuan; Tu, Sanfang; Li, Yuhua; Zhang, Leping; Cheng, Yifei; Xue, Song; Zhang, Yongping; Wang, Bin; Zheng, Huyong; Nishio, Nobuhiro; et al. (Frontiers in Hematology, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HCT) is a standard treatment for relapsed/refractory B-cell acute lymphoblastic leukemia (r/r B-ALL). However, about 30-40% of patients still relapse after HCT. Chimeric antigen receptor-modified T-cells (CAR-T) therapy has been proven effective in the treatment of relapsed or refractory B-ALL. We report a cohort of 30 B-ALL patients, who relapsed after HCT and were enrolled in the 4SCAR2.0 study, receiving CD19 CAR-T cells alone (20 patients), or two types of CAR-T cells targeting CD19, CD22, CD38 or CD123 antigens (10 patients), depending on the tumor antigen expression profile. These patients had extramedullary (EM) relapse or bone marrow (BM) relapse, or both. Based on the GVHD history, donor chimerism, and the available T-cell source, 25 patients received allogeneic donor CAR-T cells, and 5 patients received autologous CAR-T cells. All the twenty patients receiving a single CD19 CAR-T cell infusion achieved a minimal residual disease (MRD) remission within 60 days. The remaining 10 patients, due to low CD19 antigen expression profile, received 2 CAR-T cell products given on the same day, and 9 of 10 achieved CR and 1 had disease progression within 60 days. After CAR-T infusion, no cytokine release syndrome (CRS) was observed in 14 patients, and 16 patients experienced grade 1 CRS, and there was no neurotoxicity. Seventeen of the 30 patients who achieved remission (57%) remained in continuous remission following CAR-T cells with a median follow-up of 2 years and a median duration of remission of 12 months (range 2.8 - 67 months). Twelve out of 29 patients (41%) who achieved remission, subsequently relapsed at a median of 6.3 months (range 2.8-22.3 months) after CAR-T cells. In summary, 29 patients (97%) achieved MRD negative remission within 60 days of therapy with a single or double CAR-T cell infusion, and 7 patients remained in durable remission (7/30, 23%) after more than 2 years of follow-up. Thus, the tumor antigen profile-guided precision 4SCAR2.0 regimen for the treatment of r/r B-ALL after allo-HCT was highly effective with low toxicity. This approach warrants extended follow-up and expanded studies.